ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS PADA MATERI BENTUK PANGKAT, AKAR, DAN LOGARITMA DI SMK - Anggraini, Padhila; Prahmana, Rully Charitas Indra (Journal of Honai Math, 2018)
This study aims to determine the understanding mathematical ability oftenth-grade vocational high school in making the exponent, squareroot, andlogarithm. This research method used is Qualitative Descriptive. This abilityis known after all the student complete ten questions given instrument testwas finding in the form of 10 questions understanding mathematicalcapability that has valid and reliable. The subjects were 19 student of class Xadministrative office in SMK Muhammadiyah 2 Bantul in the academic year2017/2018. This result of research show that less of understandingmathematical student of tenth-grade administrative office in operation ofnumeral and problems solving.Â DOI:Â https://doi.org/10.30862/jhm.v1i1.716